Performance Evaluation of G2T FSO Link Under Various Weather Conditions - A. Mabrouk, Wafi; F.L Abdullah, M.; S.M Gismalla, M. (International Journal of Engineering and Technology, 2018)
FSO technology has attracted a lot of popularity for a variety of applied telecommunication fields. It presents a wide range of advantages that place it in the frontier of high data rates applications, last mile problem and bottleneck issues. It has been preferred for its ease of deployment without fiber cables, no extra tariff fees, cost-effectiveness, and efficiency. FSO excels in performance when compared to contemporary RF technology. On the other hand, there is an increased demand for alternative rail communications solutions. In order to deliver a safer, reliable and fast internet access. In this paper, performance evaluation of a ground-to-train Free Space Optical link communication (G2T FSO) was performed. The system was simulated at 2.5 Gb/s link under several weather conditions. Receiver and geometrical loss were included as well. Furthermore, performance was evaluated in terms of received power, Q factor, BER and eye diagram. Substantial vulnerability to severe fog attenuation was found. Although the system was able to operate with acceptable eye height with min BER of 10-38.Â Â